Ibn Taymiyya (Makers of the Muslim World) - Hafiz Abdul Karim, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2021)
The prevailing trend of studies on Ibn Taymiyya in the Western scholarship has always been segmented in nature. It may have begun with Henri Laoust, who examined the scholar's social and political theories in his Essai (1939). Following him is a plethora of studies covering various aspects of Ibn Taymiyya, ranging from examinations of his life and views to critical study upon his extensive works. Jon Hoover's Ibn Taymiyya, however, detaches away from the said approach. The author instead has offered a much wider assessment of every known aspect of Ibn Taymiyya's legacy. This could have come from the fact that this book is part of the Makers of the Muslim World series, where it focuses to bring scholarly series of biographical books concerning Muslim figures throughout history.